Guidelines for the Academic Administration for Excellency of Holy Redeemer Khon Kaen Province - Ratsuisaen, Boonjun (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were: To study the current condition and the necessity of academic administration towards excellence at Holy Redeemer Khon Kaen Province. The research was divided into 2 phases. The first phase examined the current situation and the need for academic administration of Holy Redeemer Khon Kaen Province. According to the seven academic frameworks, the sample group used in this research were 175 administrators and teachers of Holy Redeemer Khon Kaen Province, which were obtained by simple random sampling. The tools were a 5 level estimation questionnaire with a reliability of 0.95. The statistics used percentage, mean and standard deviation by interviewing 5 qualified persons. The results of the research were found that: Current conditions and the necessity of academic administration of Holy Redeemer Khon Kaen Province overall, at a high level considering each aspect, it was found that the most important need for academic administration is media and technology development for education, followed by curriculum management; teaching management educational supervision and research to improve educational quality, respectively. Guidelines for academic administration excellence at Holy Redeemer Khon Kaen Province are: 1) Developing learning resources in schools as a base for effective good news announcements, 2) Develop educational institutions curriculum according to the core curriculum of basic education and needs of society, local communities, 3) Inspect, evaluate, improve and develop educational institutions' curricula. with participation of all concerned parties, 4) organize a meeting to exchange ideas in organizing learning activities and give the community an opportunity to participate in learning management, 5) prepare extra-curricular projects for students to develop thinking skills, 6) Supervision of teaching and learning in schools according to the supervision system and process and 7) Supervision and follow-up to assist teachers in conducting classroom research.